Relationship commitment of Portuguese lesbian and gay individuals: examining the role of cohabitation and perceived social support - Rodrigues, D. L. (2018)
Lesbian and gay (LG) individuals strive to form stable relationships, and most of them are successful in doing so. Because successful relationships have benefits for psychological well-being, it is important to investigate factors that help people in same-sex relationships to achieve stable and committed relationships. The Investment Model (IM) proposes commitment to be predicted by satisfaction, quality of alternatives, and relationship investments. We extend this model by proposing two additional variables—cohabitation and social support. Cohabitation is a particularly important relationship marker for LG individuals, and its role on same-sex relationship commitment may be linked to the perception of greater support from close family and friends. In a cross-sectional study conducted in Portugal (N = 534, 62.4% gay men and 37.6% lesbian women; Mage = 29.64 years, SD = 8.30), we tested a multigroup structural equation model linking cohabitation to perceived social support from close network members (family and friends) and to relationship commitment, via the IM variables. The results showed that cohabitation was positively associated with perceived social support from both parents and friends. Friend support and its association with satisfaction mediated the association between cohabitation and commitment for both gay men and lesbian women. However, there were differences between LG individuals. Support from parents was positively associated with satisfaction and negatively associated with perceived quality of alternative situations to the relationship, but only for gay men. Support from friends was positively associated with satisfaction for both lesbian women and gay men while also positively associated with relationship investments for gay men. These results are a relevant addition to the literature by showing the importance of cohabitation and social support from parents and friends for same-sex relationship outcomes, possibly acting as buffers against different sorts of negative experiences.